ANALISA CADANGAN DEVISA INDONESIA TAHUN 1990-2016 - Dessy Dianita; Idah Zuhroh (Program Studi Ekonomi Pembangunan, 2018)
Foreign exchange reserves are a transaction tool in international trade, a tool to maintain monetary stability (especially exchange rates), a tool to pay off government foreign debt, and also a savings owned by the state. The purpose of this study is to analyze in the short and long term the influence of the exchange rate, BI rate, gross domestic product, and economic crisis on foreign exchange reserves both partially and simultaneously. In conducting this research, researchers used error correction model which included stationary test, cointegration test, short-term regression test, classic assumption test, long-term regression test, and determination coefficient test. Partial test results both in the short and long term can be seen that the exchange rate has a significant and negative effect on foreign exchange reserves, in the short term the BI rate does not have a significant effect and has a negative relationship to foreign exchange reserves and in the long run the BI rate has no effect significant and positively related to foreign exchange reserves, gross domestic product has a significant and positive impact on foreign exchange reserves both in the short and long term, and the economic crisis has a significant and positive impact on foreign exchange reserves both in the short and long term.Keywords : economic crisis, exchange rates, foreign exchange reserves, interest rates, gross domestic product